A MODEL FOR PRODUCTIVE WAQF DEVELOPMENT IN EMPOWERING FISHERMEN ON THE RANAI COASTLINE - Siska Desmiyanti; Said Muhammad Rahimin; Nurdian Setiawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the management of productive waqf assets and their relationship to fishermen empowerment in the coastal community of Ranai, Natuna Regency, one of Indonesia's most strategically significant yet economically marginal maritime border territories. The study aims to analyze the current condition of waqf asset utilization and to construct a productive waqf development model suited to the empowerment of approximately 3,800 small-scale capture fishermen operating in the area. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that waqf management in Ranai remains entirely consumptive, governed through informal and unaccountable nazir arrangements, with no institutional linkage to fishermen welfare. In response, this study constructs a four-pillar productive waqf development model encompassing asset legalization, nazir professionalization, productive utilization programming, and beneficiary empowerment delivery. The model demonstrates direct alignment with SDG 1 on poverty eradication, SDG 8 on decent work and economic growth, SDG 10 on reduced inequalities, and SDG 16 on just and accountable institutions, offering a transferable framework for Islamic social finance-driven community empowerment in Indonesia's coastal border regions.